2009
DOI: 10.1111/j.1365-3016.2009.01059.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality and equality in obstetric care: racial and ethnic differences in caesarean section delivery rates

Abstract: We sought to examine racial/ethnic differences in deliveries by caesarean section (CS) over time, particularly among women at low risk for this procedure. To do so, we conducted a retrospective cohort study at the University of California, San Francisco, a tertiary care academic centre. Births occurring between 1980 and 2001 were included in the analyses. Women with multiple gestations, fetuses in other than the cephalic presentation or with other known contraindications to vaginal birth were excluded. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
58
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 36 publications
5
58
2
Order By: Relevance
“…As expected, 13 the strongest independent predictor of cesarean delivery was prior cesarean delivery. Although the American College of Obstetricians and Gynecologists recommends that most pregnant women with a history of 1 low, transverse cesarean delivery should be counseled to consider vaginal birth after cesarean delivery (VBAC), 9 we found that VBAC was very uncommon.…”
Section: Discussionsupporting
confidence: 81%
“…As expected, 13 the strongest independent predictor of cesarean delivery was prior cesarean delivery. Although the American College of Obstetricians and Gynecologists recommends that most pregnant women with a history of 1 low, transverse cesarean delivery should be counseled to consider vaginal birth after cesarean delivery (VBAC), 9 we found that VBAC was very uncommon.…”
Section: Discussionsupporting
confidence: 81%
“…10,12 Yet, the reasons for these disparities in overall rate and indication remain unknown. 10,11,32 Although some have hypothesized minority women are at greater risk of cesarean delivery for “subjective” indications such as NRFS, 10 our data do not support this hypothesis. This finding is consistent with data from a 1997–2002 California cohort in which, although specific labor and delivery practices could not be examined, racial differences in cesarean delivery rate were not fully explained by delivery hospital or physician.…”
Section: Discussioncontrasting
confidence: 76%
“…Disparities have been suggested to be attributed to differences in healthcare quality, care during pregnancy and labor, and probably birth against a background of distinct genetic influences [13,14]. Disparities were not found to be due to differences in maternal age, parity, socioeconomic status, educational achievement beyond college, marital status, pre-existing chronic disease, gestational age, newborn gender, or birth weight, or to other significant independent predictors of cesarean delivery such as pre-eclampsia or macrosomia [17,22,23].…”
Section: Discussionmentioning
confidence: 98%